2021
DOI: 10.1212/wnl.0000000000011832
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Cholinesterase Inhibitors on Cognitive Decline and Mortality

Abstract: Objective:To investigate whether Cholinesterase inhibitors (ChEIs) are associated with slower cognitive decline in Alzheimer’s dementia, and decreased risk of severe dementia or death.Methods:Alzheimer’s dementia patients from the Swedish Dementia Registry (SveDem) starting on ChEIs within three months of the dementia diagnosis were included and compared to non-treated Alzheimer’s dementia patients. In a propensity score matched cohort, the association between ChEI-use and cognitive trajectories assessed by MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 49 publications
2
79
0
4
Order By: Relevance
“…Currently, marketed AD therapeutics are limited to two different categories of symptomatic therapies: acetylcholinesterase inhibitors (AChEIs) and the NMDA antagonist memantines. A recent study where 11,652 Alzheimer's dementia patients using AChEIs were compared to 5826 non-AChEI users in a 5-year follow up, demonstrated that the AChEIs-users had higher MMSE and a lower mortality rate than non-users [74]. Additional studies have shown that treatment using AChEIs is associated with reduced mortality in AD patients [75,76], a reduced risk for stroke [76], and a 37% reduction of cardiovascular events in persons with dementia treated with AChEIs [77].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, marketed AD therapeutics are limited to two different categories of symptomatic therapies: acetylcholinesterase inhibitors (AChEIs) and the NMDA antagonist memantines. A recent study where 11,652 Alzheimer's dementia patients using AChEIs were compared to 5826 non-AChEI users in a 5-year follow up, demonstrated that the AChEIs-users had higher MMSE and a lower mortality rate than non-users [74]. Additional studies have shown that treatment using AChEIs is associated with reduced mortality in AD patients [75,76], a reduced risk for stroke [76], and a 37% reduction of cardiovascular events in persons with dementia treated with AChEIs [77].…”
Section: Discussionmentioning
confidence: 99%
“…Although no disease-modifying treatments are available for clinical AD, AchE inhibitors have been shown to produce modest improvements in cognitive function and global function scores. 15 - 17 ) Additional analysis has also shown reduction in mortality in patients prescribed AChE inhibitors. 17 , 18 ) Three AChE inhibitors (donepezil, galantamine, and rivastigmine) have been approved by the Food and Drug Administration (FDA) to slow the progression of cognitive decline in patients with mild-to-severe AD.…”
Section: Acetylcholine and Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…Maria Eriksdotter 1,2 The article by Gustavsson et al 1 addresses the important question how to handle new medications with focus on drug candidates that reduce Aβ or tau in the brain, for individuals with Alzheimer's disease (AD), where the need for a diseasemodifying drug is enormous.…”
Section: Commentary To 'Novel Drug Candidates Targeting Alzheimer's Disease: Ethical Challenges With Identifying the Relevant Patient Popmentioning
confidence: 99%
“…The current medications for AD, the cholinesterase inhibitors, have been shown to be persistingly better with slower decline in treated than in untreated (Xu et al) but the decline is not halted. 2 The effects on cognition by the recently FDA-approved drug aducanumab are debatable.…”
Section: Commentary To 'Novel Drug Candidates Targeting Alzheimer's Disease: Ethical Challenges With Identifying the Relevant Patient Popmentioning
confidence: 99%